The macroeconomic impact of the income tax reductions in Malta - Aaron G. Grech (Central Bank of Malta, 2015)
This paper presents estimates of the possible macroeconomic impact of the reductions in income tax introduced in the Budgets for 2013 and 2014. The simulations are based on the structural macro-econometric model described in Grech and Micallef (2014). The impact of the reductions on Government revenue, estimated at 0.7% of GDP, is computed using data on chargeable income under the different tax bands from the Inland Revenue Department as at 2013, with future income projected using Central Bank forecasts.
Keywords: E62; H20; C5; 330